2011
DOI: 10.1371/journal.pone.0026736
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Stable Plastidic-Type Ferredoxin-NADP(H) Reductase in the Pathogenic Bacterium Leptospira interrogans

Abstract: Leptospira interrogans is a bacterium that is capable of infecting animals and humans, and its infection causes leptospirosis with a range of symptoms from flu-like to severe illness and death. Despite being a bacteria, Leptospira interrogans contains a plastidic class ferredoxin-NADP(H) reductase (FNR) with high catalytic efficiency, at difference from the bacterial class FNRs. These flavoenzymes catalyze the electron transfer between NADP(H) and ferredoxins or flavodoxins. The inclusion of a plastidic FNR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 68 publications
3
21
0
Order By: Relevance
“…These results indicated that FNRs from the evolutionarily diverse classes of cyanobacteria had different binding affinity for NADPH and catalytic efficiency towards the ferricyanide reduction. In addition, it was observed that the specific activity of FNR using NADPH (375 μM) was 23-fold higher than NADH (2 mM), demonstrating that, like other FNRs [31,34], FNR from PCC7942 also prefers NADPH over NADH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that FNRs from the evolutionarily diverse classes of cyanobacteria had different binding affinity for NADPH and catalytic efficiency towards the ferricyanide reduction. In addition, it was observed that the specific activity of FNR using NADPH (375 μM) was 23-fold higher than NADH (2 mM), demonstrating that, like other FNRs [31,34], FNR from PCC7942 also prefers NADPH over NADH.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore FNR from PCC7942 should have the characteristic FAD absorption spectrum. The UV/vis spectrum of FNR clearly showed two peaks at 385 and 455 nm, and a shoulder at 480 nm, demonstrating that FNR is certainly a flavoprotein (Figure 3A) [31,32]. …”
Section: Resultsmentioning
confidence: 99%
“…The NADP + content was determined as the μmoles of NADPH produced by the reduction of NADP + by the dehydrogenase in the presence of glucose‐6‐phosphate (G6P) using a standard NADP + curve. The same analyses were performed with other bacterial reductases as FPR from P. carotovorum (PcFPR) and B. abortus (BaFPR) and with the plastidic type FNR from L. interrogans (LepFNR) 16 and P.sativum (PeaFNR). These FPRs and FNRs were obtained as recombinant proteins in E. coli with N‐terminal polyhistidine tags.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleotide remains attached to the enzyme after extensive dialysis and gel filtration. To elucidate if this also occurs with other FPRs or FNRs, we analyzed another subclass II FPR from Pectobacterium carotovorum , a subclass IA FPR from Brucella abortus and two different plastidic type FNRs, from P. sativum and Leptospira interrogans 16 . We observed that althought with different extent, all FPRs contain the nucleotide bound.…”
Section: Introductionmentioning
confidence: 95%
“…Such secreted products include acyltransferases, amylases, kinases, celluloses, pectinases, ADP-ribosylation enzymes, proteases, lipases, and phosphatases, which break down complex biochemical components, thus conferring survival advantages to both pathogenic as well as environmental bacteria [ 17 , 49 , 50 ]. It has been shown that Leptospira synthetizes diverse hydrolytic enzymes, such as hyaluronidase [ 51 ], catalase [ 52 ], lipases [ 53 ], putative cytochrome oxidases [ 54 , 55 ], and others like the virulence modifying proteins (VMPs) [ 56 ] and the putative Quorum sensing (QS) proteins [ 57 ], which might well be secreted by the leptospiral T2S. The presence of a T2S in Leptospira implies its role in metabolism, but it also might well be related to pathogenesis, as it has been reported for other Gram-negatives, such as the Vibrio cholerae CLT toxin [ 58 ], the E. coli LT toxin [ 59 ], the Pseudomonas aeruginosa elastase, exotoxin A, phospholipase C, alkaline phosphatase, and lipases [ 41 , 60 ], as well as other proteins in plant pathogens [ 17 ], which are all secreted through their T2S.…”
Section: Discussionmentioning
confidence: 99%